Stephen, the First Martyr, and Georgian Christian Culture - Khachidze, Lela (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2016)
Stephen the First Martyr is one of the most popular saints of the Christian church. Lots of churches were built in honor of St. Stephen over the course of centuries. Numerous frescoes, artistic paintings, hymns and homilies were dedicated to him. This distinguished saint was also especially venerated in Georgia, though his place in the history of the Georgian church and Georgian culture has not been studied so far. Among several churches erected in honor of St. Stephen, there is a church, which is one of the oldest in Mtskheta, built on the spot where the Georgian nation was baptized, at the confluence of the Mtkvari and Aragvi rivers. The Urbnisi and Khirsi churches founded by the Assyrian Fathers(VI c.) are named after Stephen the First Martyr. The fresco representations of St. Stephen are found in Ateni Sioni, Betania, Tsromi and Nakipari amongst others. The toponym “Stepantsminda” is associated with the name of Stephen the First Martyr who has been mentioned in the Georgian church and old Georgian literature since ancient times. The service of St. Stephen is included in the oldest liturgical books preserved in the Georgian language – Jerusalemite Lectionary and the Oldest Iadgari. Special interest in St. Stephen is revealed by the tenth-century Georgian writer – Stephane Sananoisdze-Chkondideli, who is an author of a small-size hymn dedicated to St. Stephen. He translated from Greek the Praise to St. Stephen the First Martyr composed by Gregory of Nyssa. The data about Stephen the First Martyr, his relics and the oldest church related to the saint have been preserved in original Georgian hagiography too. In this paper, TheLife of St. Nino, the Martyrdom of St. Abo and TheLife of George the Athonite are considered in this context.